Eshche raz k voprosu o porogovoi kontseptsii - Smirnov, M. R. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The author introduces a reader into the essense of the new concept of the complete biopower spectrum in connection with the traditional interpretations of the "tresholds" concepts. He shows quite new perspectives of sports training organization basing on the methodological opportunities of his innovational ideas of "pulse structure" and their role in training loads efficiency's improvement.